2020
DOI: 10.1055/s-0040-1721176
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile and Antibiotic Sensitivity Pattern of Clinical Isolates in a Tertiary Cancer Care Center in the Northeast India

Abstract: Background This study was performed to determine the bacteriological profile and antibiotic sensitivity pattern of culture samples of patients with cancer at our institute. The study was undertaken to formulate an antibiotic policy for the treatment of infection in these patients. Materials and Methods The study was performed in the Department of Microbiology of a regional cancer center during the period from January 2017 to December 2017. Samples were collected under all aseptic precaution, and they were proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Ten out of the 13 (77%) positive blood cultures for bacteria during induction were due to gram-negative organisms. This is consistent with reports from other centres in India 14 15. Gram-positive infections are more common in Western countries, and they have a lower incidence of MDR infections than LMICs 9 10 12 13…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Ten out of the 13 (77%) positive blood cultures for bacteria during induction were due to gram-negative organisms. This is consistent with reports from other centres in India 14 15. Gram-positive infections are more common in Western countries, and they have a lower incidence of MDR infections than LMICs 9 10 12 13…”
Section: Discussionsupporting
confidence: 90%
“…Gram-negative septicaemia has higher mortality than gram-positive septicaemia and is more likely to be caused by multidrug resistant (MDR) bacteria 11–13. Therefore, a neutropenic diet is theoretically more likely to impact low-income and middle-income countries (LMICs) where gram-negative infections are more common, and colonisation rates with MDR gram-negative bacteria in the gut are high 14–17…”
Section: Introductionmentioning
confidence: 99%
“…Studies done by Talukdar et al 17 in 2023 among pediatric FN malignancy patients, showed only 7% A. baumannii which is far less than our study, another similar study by Babu KG et al 3 in 2016 showed 15.62% A. baumannii isolation.…”
Section: Discussioncontrasting
confidence: 64%
“…Similar findings were reported in other studies done on neutropenic patients harboring MDR organisms. 27 28 In our study, most of the MDR Gram-positive organisms were sensitive to vancomycin, whereas Garg et al noted that more than 50% of MDR Gram-positive organisms were vancomycin resistant. 29…”
Section: Discussionmentioning
confidence: 49%